Problems of Translating Literary Terms - Khatamova Dilfuza Abduvakhabovna (Scientific Trends, 2023)
The problem of identification and equivalence in the interpretation of literary terms remains relevant to this day. The interpretation of infused and translated established terms became the subject of this article. The article is devoted to solving the problems identified by the subject of the study. The comparative-historical method was chosen for the study.
Keywords: literary type, type, genre, epic, lyrics, drama, drama, tragedy, novel, story, short story, paramia, aphorism.